A Lifelong Smoker with Hypopituitarism: Rethinking the Hypothesis of a Tumor in the Hypophysis. (22nd April 2012) - Mathioudakis, Nestoras; Quinones-Hinojosa, Alfredo; Salvatori, Roberto; Basaria, Shehzad
Abstract : Pituitary adenomas are the most common cause of a sellar mass. Metastases to the pituitary gland, a rare occurrence, may mimic benign pituitary adenomas. We report here a case of a 61-year-old woman with an 80-pack-year smoking history who presented with headache and diplopia. Visual field testing demonstrated bitemporal hemianopsia. Pituitary MRI revealed a 2.0 cm sellar mass impinging upon the optic chiasm. Hypopituitarism was present, with no evidence of diabetes insipidus. The patient was referred to our service for transsphenoidal resection of a presumed pituitary macroadenoma. As part of her preoperative evaluation, a chest radiograph was obtained, which showed a large hilar mass. In light of the patient's extensive smoking history, the differential diagnosis was expanded to include metastatic lesion to the sella. Transsphenoidal resection of the tumor was performed and histopathology revealed small cell carcinoma. The patient received chemotherapy, but died 18 months later due to widespread brain metastases. Although the presence of diabetes insipidus may help to discriminate between pituitary adenomas and metastatic lesions, this is not a sensitive finding. This case illustrates the need for maintaining a high index of suspicion for pituitary metastasis in patients with known risk factors for malignancy.